Design and Performance Analysis of MCPC and P4 Waveforms for OFDM based Radar System - Huang, D.; Tang, J.; Xu, L.; Wu, Y. (Společnost pro radioelektronické inženýrství, 2024)
This study aimed to investigate the performance of Multicarrier Phase Coding (MCPC) and P4-encoded waveforms. Researchers explored the unique properties of these signals, focusing on aspects like phase distribution, autocorrelation, power spectral density for P4 encoding, and aperiodic autocorrelation and ambiguity function for MCPC signals. The findings identified optimal MCPC sequences with reduced peak-to-mean envelope power ratios (PMEPR), improving signal performance. Complementary codes based on permutation were also generated and analyzed for MCPC sequences. The study utilized an improved genetic algorithm to develop new and improved waveforms, underscoring the importance of techniques like optimal sequence permutation, complementary sequences, and classical window frequency weighting in enhancing signal performance.
Keywords: MCPC; P4 phase code; autocorrelation function; ambiguity function; improved gene algorithm; classical window frequency weighting